Sprint biomechanics assessment with low-cost systems: a reliability study - Mildenberger, C.; Aragona, A.; Guissani, C.; Panci, N.; Delgado-García, G. (Sport Sciences for Health, 2024)
The individual determination of force-velocity and power-velocity profiles during sprint is of great interest to coaches and sports physiotherapists. As a very short action, sprint evaluation requires a sufficiently accurate and reliable system. The aim of this study was to analyze the reliability of the free software Kinovea®, compared to the MySprint App (Apple Inc, USA). Thirty-one soccer players were evaluated and a comparative study was carried out, where 62 sprints of 30-m were analyzed by two rates: experienced and non-experienced. Vertical poles were placed at 2.5, 5, 7.5, 10, 15, 20, 25 and 30 m. All the sprints were recorded in slow motion and HD image quality. Comparisons of partial and total times were made, in addition to force, velocity and power outputs. No differences were shown between the two measurement methods for the different sprint times (ICC = 0.676-0.941, P < 0.001). The intra-rater reliability of total time in the experienced rater was almost perfect: ICC = 0.993 for Kinovea and 0.984 for the MySprint app; the intra-rater reliability for non-experienced one was 0.833 for Kinovea and 0.862 for the MySprint app. Comparing both methods, the ICC was 0.896. There were no significant differences between the variables force, velocity and power (P > 0.05). This study shows that Kinovea + Excel spreadsheet is a reliable method, also an accessible and low-cost option for sport professionals. However, experience using the software is required, but not for the use of the MySprint app, which is an advantage for non-experienced testers.